Biomechanical analysis of maxillary posterior three unit bridge supported misial straight implant and distal tilted implant - Liu, Guanqi; Deng, Shudan; Chen, Xiaoyan; Lin, Jiahui; Liu, Runheng (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThis study aims to investigate the stress distribution in bone tissue, implant, abutment, screw, and bridge restoration when the mesial implant is placed axially and the distal implant is inserted at varying angles in the posterior maxillary region with free-end partial dentition defects, using three-dimensional finite element analysis.Materials and methodsCone-beam computed-tomography were utilized to create 3D reconstruction models of the maxilla. Stereolithography data of dental implants and accessories were used to design a three-unit full zirconia bridge for the maxillary model. The 3D models were imported into ANSYS Workbench 23.0 software for mesh generation and material property definition. Five different distal implant implantation directions were designed: Inner Tilting 30° group, Inner Tilting 17° group, Parallel group, External Tilting 17° group, and External Tilting 30° group. The models consisted of cortical bone, trabecular bone, implants, abutments, central screws, prosthesis screws, and prostheses. Material properties were assumed to be isotropic, homogeneous, and linearly elastic. The maxillary models were subjected to strict fixation restrictions, and the implants were considered fully osseointegrated. Two loading types were set in ANSYS Workbench 23.0: a vertical load of 300N and a lateral load of 300N at a 45°angle to the implant.ResultsUnder vertical loading, the parallel group exhibited the lowest maximum stress across all implants, crowns, abutments and screws. Greater tilt angles increased abutment stress, with the external tilting 30° group reaching 1,426 MPa (close to titanium alloy’s yield strength). Smaller angles of both external tilting and inner tilting shifted stress to implants from abutment and screw. During lateral loading, the external tilting 30° group showed catastrophic stress escalation (abutment: 8,612 MPa), exceeding titanium’s yield limit. Bone stress remained physiological except for the internal tilting 30° group under lateral loading (142 MPa).ConclusionThe parallel group demonstrated the least stress accumulation in all components and bone tissues. Internal tilting of the distal implant is biomechanically preferable to external tilting, and a smaller tilt angle is recommended when external tilting is necessary. This study provides valuable reference data for optimizing implant angulation in patients with the loss of three posterior maxillary teeth, potentially reducing long-term complications associated with implant-fixed bridges.